AEG‐1 participates in TGF‐beta1‐induced EMT through p38 MAPK activation. (23rd May 2013) - Wei, Jiali; Li, Zhuori; Chen, Wenfang; Ma, Chunyang; Zhan, Feng; Wu, Wei; Peng, Youming
Abstract Epithelial–mesenchymal transition (EMT) is an important cellular event in organogenesis, cancer and renal tubulointerstitial fibrosis. Transforming growth factor‐beta1 (TGF‐beta1) is the key inducer of EMT and the p38 mitogen‐activated protein kinases (p38 MAPK), an major intracellular signal transduction pathway is involved in TGF‐beta1‐induced EMT. Astrocyte elevated gene‐1 (AEG‐1) represents an chief genetic determinant regulating multiple events in tumorigenesis. Our present study is to explore the role of AEG‐1 in TGF‐beta1‐induced p38 MAPK activation and EMT process in human renal tubular epithelial (HK‐2) cells. The protein expressions of AEG‐1, the markers of EMT and p38 phosphorylation were measured by Western blot. The protein expression of AEG‐1 was increased in HK‐2 cells treated with TGF‐beta1. Knockdown of AEG‐1 potently inhibited phosphorylation of p38 MAPK and reversed TGF‐beta1‐induced EMT. Over‐expression of AEG‐1 via AEG‐1 transfection elicited p38 MAPK phosphorylation and promoted EMT. The effects of AEG‐1 during EMT were blocked by a p38‐specific inhibitor. Our findings suggest that AEG‐1 plays an important role in TGF‐beta1‐induced EMT through activation of p38 MAPK in proximal tubular epithelial cells.